Wet nanomilling of naproxen using a novel stabilization mechanism via zirconium complexation - Maar, Scott; Damm, Cornelia; Peukert, Wolfgang (Advanced Powder Technology, 2022)
Using a novel electrostatic stabilization mechanism that utilizes complexation of Zr(IV) species by carboxylic acid groups at the particle surface, the true grinding limit of monocrystalline naproxen nanoparticles was identified at 30 nm under an optimized naproxen/Zr(IV)-salt formulation. In a stirred media mill, we studied the influence of stress energy and number of stress events by varying the milling bead diameter. Small milling beads provide a compromise between sufficiently high stress energy and stress number and are beneficial for nanomilling of naproxen in terms of grinding kinetics. It is shown that the product particle size can be controlled by adjusting the colloidal stability via the Zr(IV) concentration. Regardless of formulation properties, particle fracture propagates along the grain boundaries as revealed by crystallite size analysis. Investigations of the solvent phase and the particle geometry reveal that mechanical stress leads to enhanced solubility of the drug, which in return promotes recrystallization and thus particle growth. The solubility can be reduced by lowering the process temperature and stabilizer concentration. In contrast to inorganic nanoparticles, which are almost free of lattice imperfections at the true grinding limit, we find a clear indication of lattice strain in the stressed naproxen nanoparticles. Since the nanoparticle yield is still limited to 40% due to particle ripening, fast removal of the nanoparticles from the mill must be a further next step to be solved in nanoparticle processing.
CRIS-Team Scopus Importer:2022-08-12
Keywords: Colloidal stability; Grinding limit; Naproxen; Solubility; Stirred media ball mill